Involvement of Arabidopsis phospholipase D δ in regulation of ROS-mediated microtubule organization and stomatal movement upon heat shock - Song, Ping (Journal of experimental botany, 2020)
© The Author(s) 2020. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.